Experimental study on the thermal storage performance of phase change materials embedded with additively manufactured triply periodic minimal surface architected lattices. (15th December 2022) - Zhang, Tao; liu, Fei; Deng, Xing; Zhao, Miao; Zhou, Hailun; Zhang, David Z.
Highlights: A novel design method of thermal conductivity enhancer (TCE) in composite phase change materials. Manufacturing deviations of SLMed TCE were evaluated by microCT. A comprehensive study was carried out to determine the mechanism of heat storage performance improvement experimentally. An optimization strategy for thermal conductivity enhancement of lattice structures was provided by the design priorities of volume fraction, pore size and cell type. Abstract: Porous structures are widely used as thermal conductivity enhancers (TCEs) for phase change materials (PCMs) in thermal management systems (TMSs) and thermal storage systems (TSSs). The heat transfer performance of PCMs filled with traditional metal foams has been extensively investigated both numerically and experimentally. Additive manufactured (AM) lattices with controllable structures have attracted extensive and continuously growing attention due to their high specific strength, interconnected pores, and high thermal conductivity, outperforming both conventional stochastic metal foams and honeycomb with great potential in TSSs. In this work, lattices with novel continue surface structures were inserted into PCMs for heat transfer augmentation. Using the implicit function of triply periodic minimal surfaces (TPMS), nine lattices with varied relative density, cell sizes, and cell types were designed and fabricated by selective laser melting (SLM) using AlSi10Mg. PCMs embedded by lattices were built by the casting method and adopted in the visualized thermal storage experiment to evaluate the geometric effect on the melting interface, temperature variation, and thermal storage performance under a constant heating power of 10 W. The results showed that the pure paraffin took the longest time of 70 min to completely melt, however, the embedding of a TPMS with a relative density of just 10% reduced the melting time by nearly 20 min. The embedding of TPMS period porous aluminum (PPA) improved the response rate of the paraffin wax (PX) to temperature by accelerating the melting pace and advancing the onset of latent heat energy storage. The relative density plays a dominant role in enhancing thermal conductivity; nonetheless, excessive addition will reduce the heat storage capacity and heat storage density of PCMs. The cell size and cell type could further accelerate the melting rate for more design choices and sheet-like TPMS possesses greater heat transfer potential than rod-like structure. Besides, the GS-65-20 case stored a total amount of 4181.95 J heat at the fastest rate of 1.85 J/s, which was 1.5 times the heat storage rate of the pure PCM case, showing the best-balanced performance. An optimization strategy for thermal conductivity enhancement of lattice structures was provided according to the design priorities of relative density, pore size, and cell type. Graphical abstract: Image, graphical abstract